Message Framing by Regulatory Focus on Intention to Visit Village-based Tourism Destination - Husna Putri Pertiwi; Ridha Azka Raga; Jasrial Jasrial; Mufid Salim; Ira Siti Sarah; Ivon Sandya Sari Putri (Politeknik Negeri Bandung, 2023)
The intention to visit a Village-based Tourism destination is still remaining low, especially during post-pandemic sessions. Our study wants to observe the intention to visit among several factors to fill this gap. Focus on finding marketing strategies that are more practical to increase the intention of visiting Village-based tourism destinations. Thus, this research is conducted by experimental research to examine the intention of visiting Village-based tourism using a message framing based on regulatory focus manipulation. 237 respondents participated in this study. The result shows that participants under the manipulation condition show greater intention to visit the VBT destination than those without any manipulation condition. Thereby, it indicates using a message framing through regulatory focus increases the visit intention toward village-based tourism destinations.